Long-life high-efficiency catalytic degradation of volatile organic compounds (VOCs) wet skeleton non-woven fabric, and preparation method and application thereof

CN118668513BActive Publication Date: 2026-10-16BAOJI JIAXIN FILTER MATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410702701.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-03
Publication Date
2026-10-16
Estimated Expiration
2044-06-03

AI Technical Summary

Technical Problem

[0007]虽然这些无纺布产品较好地提供催化降解挥发性有机物VOCs的功能,但由于其成型方式的制约,其循环次数低,催化时效较差也成为了制约其在空气净化领域大规模应用的缺陷之一

Benefits of technology

[0029] Subsequently, a curtain coating application was performed using a sizing agent composed of hyperbranched polyamide amine and polyacrylic acid resin. Hyperbranched polyamide amine is a hyperbranched water-based polymer material with a high adsorption and decomposition capacity for harmful substances such as formaldehyde, converting them into water and other harmless substances. It is safe, non-toxic, non-irritating, non-volatile, and has good film-forming properties, making it an excellent ultra-efficient formaldehyde remover. Therefore, after efficiently loading titanium dioxide, it was used for coating and sizing treatment to further enhance the VOCs removal effect of the nonwoven fabric. The resulting nonwoven fabric product can be used to prepare various functional air filter materials, catalytic materials, adsorbent materials, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118668513B_ABST
    Figure CN118668513B_ABST
Patent Text Reader

Abstract

The application discloses a long-life high-efficiency wet-process skeleton non-woven fabric for catalytic degradation of volatile organic compounds (VOCs) and a preparation method and application thereof, and belongs to the technical field of non-woven fabric materials.The method improves the added value and application field of the wet-process non-woven fabric through two-step surface treatment of fiber raw materials and self-assembly design of functional materials, is convenient for large-scale processing and production, and is simple in process, convenient to operate and easy to implement.The prepared wet-process skeleton non-woven fabric has a fiber fineness of 12-40 mu m, a breaking strength greater than 130 N / 50 mm, a transverse greater than 90 N / 50 mm, an air permeability greater than 3500 mm / s, a pressure difference less than 130 MPa, a stiffness longitudinal greater than 210 mg, a transverse greater than 100 mg, good air permeability, a catalytic degradation efficiency of volatile organic compounds such as formaldehyde of 99.99%, and a catalytic efficiency of more than 90% after 48 months.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nonwoven material technology, specifically relating to a long-life, high-efficiency wet-laid skeleton nonwoven fabric for catalytic degradation of volatile organic compounds (VOCs), its preparation method, and its application. Background Technology

[0002] In recent years, with the continuous improvement of people's living standards and the enhancement of environmental awareness, the market demand for the treatment of organic pollutants in the air is constantly rising. As a non-woven fabric product with high stiffness performance, wet-laid non-woven fabric is widely used as a skeleton material in composite filter elements in the fields of air purifiers, household air conditioners, automotive air conditioners, vacuum cleaners, and air purification in large clean rooms.

[0003] Traditional filter-type air purifiers primarily use fans to draw air through various stages of materials with filtration or adsorption functions to purify the air. However, after a period of use, the filter materials adsorb large amounts of organic pollutants such as formaldehyde, toluene, and benzene. These pollutants accumulate inside the purifier over time, posing a new threat to environmental hygiene. Developing air filter materials with a long-lasting function to decompose organic pollutants such as formaldehyde, toluene, and benzene can significantly reduce the content of organic pollutants in the living environment, which is of great significance for creating a new, livable microenvironment and protecting human health.

[0004] Currently, most related products on the market are formaldehyde-absorbing non-woven fabrics or formaldehyde-removing non-woven fabrics, mainly made of materials with high adsorption properties such as activated carbon and bamboo charcoal. These materials have a large number of micropores and surface areas, which can effectively adsorb formaldehyde and other small organic molecules in the air. Non-woven fabrics with catalytic degradation functions are relatively rare. Generally, catalysts (such as titanium dioxide) are blended with crosslinking agents, complexing agents, and penetrants, and then a finishing process is used to prepare non-woven fabrics with certain functions. The catalyst supported on the non-woven fabric promotes the decomposition of organic matter such as formaldehyde and converts it into harmless substances.

[0005] Chinese patent application CN202211041382.3 discloses a photocatalytic spunbond nonwoven fabric and its preparation method. By adding a photocatalyst, under light irradiation, a photocatalytic reaction similar to photosynthesis is generated, producing highly oxidizing free hydroxyl radicals and reactive oxygen species, exhibiting strong photo-oxidation and reduction capabilities. It can kill bacteria and decompose organic pollutants, breaking down organic matter into harmless water (H2O) and carbon dioxide (CO2), achieving functions such as antibacterial properties, air purification (formaldehyde removal), odor removal, mildew prevention, self-cleaning, UV protection, and antistatic properties.

[0006] Chinese patent application CN202222591619.7 discloses a formaldehyde removal air filter material, including an activated carbon layer, a nanofiber filter layer, a hot melt adhesive layer, and a meltblown nonwoven fabric layer. The activated carbon layer is a wet-laid skeleton nonwoven fabric uniformly loaded with activated carbon. The nanofiber filter layer is an aqueous polymer nanofiber membrane attached to the activated carbon layer. The hot melt adhesive layer bonds the nanofiber filter layer and the meltblown nonwoven fabric together.

[0007] While these nonwoven fabric products effectively catalyze the degradation of volatile organic compounds (VOCs), their low cycle life and poor catalytic efficiency, due to limitations in their molding process, are among the drawbacks restricting their large-scale application in air purification. To date, no research or preparation methods have been reported for the industrial-scale production of wet-laid nonwoven fabrics with long lifespan and high efficiency in catalytic degradation of VOCs. Developing a wet-laid nonwoven fabric with long lifespan and high efficiency in catalytic degradation of VOCs is a pressing technical problem that needs to be solved and will have broad market application prospects. Summary of the Invention

[0008] This invention aims to fill the market gap for industrially produced, long-life, high-efficiency wet-laid nonwoven fabrics for the catalytic degradation of volatile organic compounds (VOCs), and to meet the demand for such fabrics in modern civilian and industrial applications. It provides a long-life, high-efficiency wet-laid nonwoven fabric for VOCs and its preparation method. This invention's long-life, high-efficiency wet-laid nonwoven fabric for VOCs possesses high air permeability while also exhibiting high stiffness due to its unique structural design, ensuring both mechanical properties and gas permeability. Furthermore, because its main chemical structure is polyester fiber, this nonwoven fabric also possesses advantages such as chemical stability, resistance to photoaging, and low moisture regain.

[0009] To achieve the above-mentioned technical objectives, the technical solution adopted by the present invention is as follows:

[0010] A method for preparing a wet-laid skeleton nonwoven fabric with long lifespan and high efficiency for catalytic degradation of volatile organic compounds (VOCs) includes the following preparation steps:

[0011] (1) Wet ion etching surface treatment: Keratin solution is sprayed onto the surface of fiber raw material and dried at a constant temperature after spraying; then crosslinking agent solution is sprayed and dried at a constant temperature. The crosslinking agent completes crosslinking during the drying process; then the dried fiber raw material is immersed in acid solution and surface etching is performed by acid immersion. A large number of micropores and mesopores are generated in the areas not covered by keratin crosslinking due to acid etching; then it is filtered and washed with water to remove excess acid from the fiber surface; then the fiber raw material is treated with alkaline washing to remove keratin. After alkaline washing, deionized water is used to wash away residual alkaline solution from the fiber surface.

[0012] (2) Plasma bombardment surface treatment: The fiber raw material obtained in step (1) is placed in a plasma device, and after vacuuming, nitrogen is used as the gas source to generate plasma by radio frequency inductive coupling to treat the fiber raw material.

[0013] (3) Preparation of self-assembled functional nanomaterials: The functional materials and nonionic surfactants were mixed in proportion and then added to a nanoball mill for grinding and dispersion to obtain self-assembled functional nanomaterials.

[0014] (4) Web forming: The fiber raw material obtained in step (2) and the self-assembled functional nanomaterial obtained in step (3) are stirred and loosened in the raw material tank in proportion to prepare a slurry. The slurry is then fully mixed with deionized water at a mass ratio of (5-25):100 and dehydrated and formed in a forming inclined screen to obtain a fiber web. The temperature and pH value of the formed fiber web are then adjusted so that the functional nanomaterials can self-assemble in the fiber web.

[0015] (5) Coating and sizing: After adjusting the temperature and pH value, quickly apply the sizing to the formed fiber web in a curtain-like manner. After the sizing is completed, heat up and cure.

[0016] (6) Post-processing: After the cured fiber web is washed with water, ultrasonically removed and defects removed, it is then subjected to thermal stretching and shaping to obtain the final product, wet-laid skeleton nonwoven fabric.

[0017] Further, the mass concentration of the keratin solution in step (1) is 10-40%. The mass ratio of the keratin solution to the fiber raw material is (1-3):100; the constant temperature drying temperature is 35-60℃, and the time is 30-180 minutes. The mass concentration of the crosslinking agent solution is 20-50%, and the mass ratio of keratin to crosslinking agent is 1:(1-10). The crosslinking agent is a dialdehyde compound or a diglycidyl ether compound. The dialdehyde compound is glyoxal or glutaraldehyde, etc., and the diglycidyl ether compound is polyethylene glycol diglycidyl ether, etc. The acid solution is one or a combination of sulfuric acid with a mass concentration of 30% or more, phosphoric acid with a mass concentration of 50% or more, hydrochloric acid with a mass concentration of 15% or more, and nitric acid with a mass concentration of 15% or more. The alkaline washing is performed at a temperature of 50-75°C for 30-120 minutes. The alkaline solution used is one or more of the following: concentrated ammonia, sodium hydroxide solution with a mass concentration of 5-15%, and potassium hydroxide solution with a mass concentration of 5-15%.

[0018] Furthermore, in step (1), the fiber raw materials are polyethylene terephthalate fibers with a length of 10-18 mm, polyethylene terephthalate fibers with a length of 3-10 mm, and vinylon fibers with a length of 3-10 mm, with a mass ratio of (3-6):(1-3):(2-3).

[0019] Furthermore, the vacuum pressure in step (2) is less than 100 Pa.

[0020] Furthermore, in step (2), the radio frequency processing power is controlled to be 200-1000W and the radio frequency is 8-15MHz, and the processing time is 100-600s under the condition of 30-110℃.

[0021] Further, in step (3), the functional material comprises titanate compounds, sodium aluminate, and chitosan, with a mass ratio of (3-5):(0-3):1; the titanate compounds are tetrabutyl titanate and / or tetrabutyl titanate phosphate; the nonionic surfactant is one or more of long-chain fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine, and polyoxyethylene alkylolamide; the mass ratio of the functional material to the nonionic surfactant is 100:(2.5-5).

[0022] Furthermore, by mass ratio, the amount of fiber raw materials and self-assembled functional nanomaterials used in step (4) is: 10-18 mm long polyethylene terephthalate fiber: 3-10 mm long polyethylene terephthalate fiber: 3-10 mm long vinylon fiber: self-assembled functional nanomaterials = (3-6):(1-3):(2-3):(0.1-2).

[0023] Furthermore, in step (4), the temperature is adjusted to 60-75℃ and the pH is greater than 10.

[0024] Furthermore, in step (5), the adhesive solution is a co-solution mixture of hyperbranched polyamide amine and polyacrylic acid resin, with a mass ratio of (8-15):1, and the curing temperature is 100-150℃.

[0025] A nonwoven fabric prepared according to the method of the present invention.

[0026] All raw materials used in this invention are commercially available.

[0027] This invention employs a two-step surface modification process for raw fiber materials. The first step involves wet etching using sulfuric acid as the etchant and keratin or polypropylene as a masking agent to modify the fiber surface. This is followed by wet etching with sulfuric acid, preserving the original structure in areas covered by keratin while etching out mesopores or micropores in areas not covered by keratin. The second step involves plasma bombardment, leaving exposed end-group sites (such as activated hydroxyl, carbonyl, or carboxyl groups) within the mesopores or micropores for chemical bonding. This improves surface wettability and adhesion. This two-step modification successfully activates the raw fiber materials, laying a solid material foundation for the efficient and stable loading of subsequent nanomaterials.

[0028] Subsequently, titanate compounds, sodium aluminate, and chitosan were used as functional materials, and nonionic surfactants were added for co-grinding, emulsification, and dispersion to obtain functional nanomaterials with a capsule structure. Deionized water was then added, and by adjusting the appropriate temperature and pH, the capsule-structured functional materials underwent demulsification. At this point, the titanate compounds tended to undergo hydrolysis in the micropores or mesopores with exposed end groups. The resulting titanium dioxide catalyst was stably loaded in these mesopores or micropores, and was not easily detached during use, thus sustaining a stable catalytic effect. This is what this invention refers to as "self-assembly."

[0029] Subsequently, a curtain coating application was performed using a sizing agent composed of hyperbranched polyamide amine and polyacrylic acid resin. Hyperbranched polyamide amine is a hyperbranched water-based polymer material with a high adsorption and decomposition capacity for harmful substances such as formaldehyde, converting them into water and other harmless substances. It is safe, non-toxic, non-irritating, non-volatile, and has good film-forming properties, making it an excellent ultra-efficient formaldehyde remover. Therefore, after efficiently loading titanium dioxide, it was used for coating and sizing treatment to further enhance the VOCs removal effect of the nonwoven fabric. The resulting nonwoven fabric product can be used to prepare various functional air filter materials, catalytic materials, adsorbent materials, etc.

[0030] In summary, the beneficial effects of this invention are as follows: The method of this invention is applicable to the preparation of wet-laid nonwoven fabrics with long lifespan and high efficiency in catalytic degradation of volatile organic compounds (VOCs), improving the added value and application fields of wet-laid nonwoven fabrics, facilitating large-scale processing and production, and featuring simple processes, convenient operation, and easy implementation. The prepared wet-laid nonwoven fabric with long lifespan and high efficiency in catalytic degradation of VOCs has a fiber fineness of 12-40 μm, a breaking strength greater than 130 N / 50 mm and a transverse strength greater than 90 N / 50 mm, an air permeability greater than 3500 mm / s, a pressure difference less than 130 MPa, and a stiffness greater than 210 mg in the longitudinal direction and greater than 100 mg in the transverse direction. All performance indicators are excellent, with good air permeability. The catalytic degradation efficiency for volatile organic compounds (VOCs) such as formaldehyde can reach 99.99%, and it can still maintain a catalytic efficiency of over 90% after 48 months. Attached Figure Description

[0031] Figure 1 Photograph of the wet-laid skeleton nonwoven fabric obtained in Example 5 of the present invention;

[0032] Figure 2 Microscopic photograph of ordinary wet-laid nonwoven fabric, Comparative Example 4;

[0033] Figure 3 This is a microscope image of the wet-laid skeleton nonwoven fabric obtained in Example 5 of the present invention. Detailed Implementation

[0034] The technical solution of the present invention will be further described below with reference to specific embodiments, but it is not limited thereto.

[0035] Example 1

[0036] A method for preparing a wet-laid skeleton nonwoven fabric with long lifespan and high efficiency for catalytic degradation of volatile organic compounds (VOCs) includes the following preparation steps:

[0037] (1) Wet ion etching surface treatment: Keratin solution is sprayed onto the surface of fiber raw material and dried at a constant temperature after spraying; then crosslinking agent solution is sprayed and dried at a constant temperature. The crosslinking agent completes crosslinking during the constant temperature drying process; then the dried fiber raw material is immersed in acid solution and surface etching is performed by acid immersion. The areas not covered by keratin crosslinking are covered by a large number of micropores and mesopores due to the acid; then it is filtered and washed with water to remove excess acid from the fiber surface; then the fiber raw material is treated with alkaline washing to remove keratin. After alkaline washing, deionized water is used to wash away residual alkaline solution from the fiber surface.

[0038] (2) Plasma bombardment surface treatment: The fiber raw material obtained in step (1) is placed in a plasma device, vacuumed, and then nitrogen is used as the gas source to generate plasma by radio frequency inductive coupling to treat the fiber raw material.

[0039] (3) Preparation of self-assembled functional nanomaterials: The functional materials and nonionic surfactants were mixed in proportion and then added to a nanoball mill for grinding and dispersion to obtain self-assembled functional nanomaterials.

[0040] (4) Web forming: The fiber raw material obtained in step (2) and the self-assembled functional nanomaterial obtained in step (3) are stirred and loosened in the raw material tank in proportion to prepare a slurry. The slurry is then fully mixed with deionized water at a mass ratio of 25:100 and dehydrated in a forming inclined screen to obtain a fiber web. The temperature and pH value of the formed fiber web are then adjusted so that the functional nanomaterials can self-assemble in the fiber web.

[0041] (5) Coating and sizing: After adjusting the temperature and pH value, the formed fiber web is quickly coated and sizing is applied in a curtain manner. After the sizing is completed, the web is heated and cured.

[0042] (6) Post-processing: After the cured fiber web is washed with water, ultrasonically removed and defects removed, it is then subjected to thermal stretching and shaping to obtain the final product, wet-laid skeleton nonwoven fabric.

[0043] The keratin solution in step (1) has a mass concentration of 10%. The mass ratio of keratin solution to fiber raw material is 3:100; the constant temperature drying temperature is 35-60℃, and the time is 30 minutes. The crosslinking agent solution has a mass concentration of 50%, and the mass ratio of keratin to crosslinking agent is 1:10. The crosslinking agent is glyoxal. The acid solution is sulfuric acid with a mass concentration of 30% or higher. The alkaline washing is performed at a temperature of 50-75℃ for 30 minutes, and the alkaline solution used is a 5% sodium hydroxide solution.

[0044] Step (1) The fiber raw materials are 10mm long polyethylene terephthalate fiber (diameter 20μm), 3mm long polyethylene terephthalate fiber (diameter 24μm) and 3mm long vinylon fiber (diameter 18μm), with a mass ratio of 3:1:2.

[0045] The vacuum pressure in step (2) is less than 100 Pa.

[0046] Step (2) control the radio frequency processing power to be 200W and the radio frequency to be 15MHz, and process for 600s at a temperature of 30℃.

[0047] Step (3) The functional material contains a titanate compound and chitosan in a mass ratio of 3:1; the titanate compound is tetrabutyl titanate; the nonionic surfactant is fatty acid polyoxyethylene ester; the mass ratio of the functional material and the nonionic surfactant is 100:2.5.

[0048] According to the mass ratio, the amount of fiber raw materials and self-assembled functional nanomaterials used in step (4) is: 10 mm long polyethylene terephthalate fiber: 3 mm long polyethylene terephthalate fiber: 3 mm long vinylon fiber: self-assembled functional nanomaterials = 3:1:2:0.1.

[0049] Step (4) Adjust the temperature to 60-75℃ and pH > 10.

[0050] In step (5), the adhesive solution is a co-solution of hyperbranched polyamide amine and polyacrylic acid resin with a mass ratio of 8:1, and the curing temperature is 100-150℃.

[0051] Example 2

[0052] A method for preparing a wet-laid skeleton nonwoven fabric with long lifespan and high efficiency for catalytic degradation of volatile organic compounds (VOCs) includes the following preparation steps:

[0053] (1) Wet ion etching surface treatment: Keratin solution is sprayed onto the surface of fiber raw material and dried at a constant temperature after spraying; then crosslinking agent solution is sprayed and dried at a constant temperature. The crosslinking agent completes crosslinking during the constant temperature drying process; then the dried fiber raw material is immersed in acid solution and surface etching is performed by acid immersion. The areas not covered by keratin crosslinking are covered by a large number of micropores and mesopores due to the acid; then it is filtered and washed with water to remove excess acid from the fiber surface; then the fiber raw material is treated with alkaline washing to remove keratin. After alkaline washing, deionized water is used to wash away residual alkaline solution from the fiber surface.

[0054] (2) Plasma bombardment surface treatment: The fiber raw material obtained in step (1) is placed in a plasma device, vacuumed, and then nitrogen is used as the gas source to generate plasma by radio frequency inductive coupling to treat the fiber raw material.

[0055] (3) Preparation of self-assembled functional nanomaterials: The functional materials and nonionic surfactants were mixed in proportion and then added to a nanoball mill for grinding and dispersion to obtain self-assembled functional nanomaterials.

[0056] (4) Web forming: The fiber raw material obtained in step (2) and the self-assembled functional nanomaterial obtained in step (3) are stirred and loosened in the raw material tank in proportion to prepare a slurry. The slurry is then fully mixed with deionized water at a mass ratio of 5:100 and dehydrated in a forming inclined screen to obtain a fiber web. The temperature and pH value of the formed fiber web are then adjusted so that the functional nanomaterials can self-assemble in the fiber web.

[0057] (5) Coating and sizing: After adjusting the temperature and pH value, the formed fiber web is quickly coated and sizing is applied in a curtain manner. After the sizing is completed, the web is heated and cured.

[0058] (6) Post-processing: After the cured fiber web is washed with water, ultrasonically removed and defects removed, it is then subjected to thermal stretching and shaping to obtain the final product, wet-laid skeleton nonwoven fabric.

[0059] The keratin solution in step (1) has a mass concentration of 40%. The mass ratio of keratin solution to fiber raw material is 1:100; the constant temperature drying temperature is 35-60℃, and the time is 180 minutes. The crosslinking agent solution has a mass concentration of 20%, and the mass ratio of keratin to crosslinking agent is 1:1. The crosslinking agent is glutaraldehyde. The acid solution is phosphoric acid with a mass concentration of 50% or higher. The alkaline washing is performed at a temperature of 50-75℃ for 120 minutes, and the alkaline solution used is a 15% potassium hydroxide solution.

[0060] Step (1) The fiber raw materials are 10 mm long polyethylene terephthalate fiber (diameter 20 μm), 3 mm long polyethylene terephthalate fiber (diameter 24 μm) and 3 mm long vinylon fiber (diameter 18 μm), with a mass ratio of 6:3:3.

[0061] The vacuum pressure in step (2) is less than 100 Pa.

[0062] Step (2) control the radio frequency processing power to be 1000W and the radio frequency to be 8MHz, and process for 100s at a temperature of 110℃.

[0063] Step (3) The functional material comprises titanate compound, sodium aluminate and chitosan in a mass ratio of 5:3:1; the titanate compound is tetrabutyl titanate phosphate; the nonionic surfactant is alkylphenol polyoxyethylene ether; the mass ratio of the functional material and the nonionic surfactant is 100:5.

[0064] According to the mass ratio, the ratio of fiber raw materials and self-assembled functional nanomaterials in step (4) is: 18 mm long polyethylene terephthalate fiber: 10 mm long polyethylene terephthalate fiber: 10 mm long vinylon fiber: self-assembled functional nanomaterials = 6:3:3:2.

[0065] Step (4) Adjust the temperature to 60-75℃ and pH > 10.

[0066] In step (5), the adhesive solution is a co-solution of hyperbranched polyamide amine and polyacrylic acid resin with a mass ratio of 15:1, and the curing temperature is 100-150℃.

[0067] Example 3

[0068] A method for preparing a wet-laid skeleton nonwoven fabric with long lifespan and high efficiency for catalytic degradation of volatile organic compounds (VOCs) includes the following preparation steps:

[0069] (1) Wet ion etching surface treatment: Keratin solution is sprayed onto the surface of fiber raw material and dried at a constant temperature after spraying; then crosslinking agent solution is sprayed and dried at a constant temperature. The crosslinking agent completes crosslinking during the constant temperature drying process; then the dried fiber raw material is immersed in acid solution and surface etching is performed by acid immersion. The areas not covered by keratin crosslinking are covered by a large number of micropores and mesopores due to the acid; then it is filtered and washed with water to remove excess acid from the fiber surface; then the fiber raw material is treated with alkaline washing to remove keratin. After alkaline washing, deionized water is used to wash away residual alkaline solution from the fiber surface.

[0070] (2) Plasma bombardment surface treatment: The fiber raw material obtained in step (1) is placed in a plasma device, vacuumed, and then nitrogen is used as the gas source to generate plasma by radio frequency inductive coupling to treat the fiber raw material.

[0071] (3) Preparation of self-assembled functional nanomaterials: The functional materials and nonionic surfactants were mixed in proportion and then added to a nanoball mill for grinding and dispersion to obtain self-assembled functional nanomaterials.

[0072] (4) Web forming: The fiber raw material obtained in step (2) and the self-assembled functional nanomaterial obtained in step (3) are stirred and loosened in the raw material tank in proportion to prepare a slurry. The slurry is then fully mixed with deionized water at a mass ratio of 13:100 and dehydrated in a forming inclined screen to obtain a fiber web. The temperature and pH value of the formed fiber web are then adjusted so that the functional nanomaterials can self-assemble in the fiber web.

[0073] (5) Coating and sizing: After adjusting the temperature and pH value, the formed fiber web is quickly coated and sizing is applied in a curtain manner. After the sizing is completed, the web is heated and cured.

[0074] (6) Post-processing: After the cured fiber web is washed with water, ultrasonically removed and defects removed, it is then subjected to thermal stretching and shaping to obtain the final product, wet-laid skeleton nonwoven fabric.

[0075] The keratin solution in step (1) has a mass concentration of 20%. The mass ratio of keratin solution to fiber raw material is 2:100; the constant temperature drying temperature is 35-60℃, and the time is 100 minutes. The crosslinking agent solution has a mass concentration of 30%, and the mass ratio of keratin to crosslinking agent is 1:3. The crosslinking agent is malondialdehyde. The acid solution is hydrochloric acid with a mass concentration of 15% or higher. The alkaline washing is performed at a temperature of 50-75℃ for 60 minutes, using a 6% sodium hydroxide solution.

[0076] Step (1) The fiber raw materials are 10 mm long polyethylene terephthalate fiber (diameter 20 μm), 3 mm long polyethylene terephthalate fiber (diameter 24 μm) and 3 mm long vinylon fiber (diameter 18 μm), with a mass ratio of 6:1.5:2.

[0077] The vacuum pressure in step (2) is less than 100 Pa.

[0078] Step (2) control the radio frequency processing power to be 400W and the radio frequency to be 12MHz, and process for 200s at a temperature of 60℃.

[0079] Step (3) The functional material contains a titanate compound, chitosan, in a mass ratio of 5:1; the titanate compound is tetrabutyl titanate phosphate; the nonionic surfactant is castor oil polyoxyethylene ether; the mass ratio of the functional material to the nonionic surfactant is 100:5.

[0080] According to the mass ratio, the ratio of fiber raw materials and self-assembled functional nanomaterials in step (4) is: 15 mm long polyethylene terephthalate fiber: 6 mm long polyethylene terephthalate fiber: 5.2 mm long vinylon fiber: self-assembled functional nanomaterials = 6:1.5:2:0.5.

[0081] Step (4) Adjust the temperature to 60-75℃ and pH > 10.

[0082] In step (5), the adhesive solution is a co-solution of hyperbranched polyamide amine and polyacrylic acid resin with a mass ratio of 10:1, and the curing temperature is 100-150℃.

[0083] Example 4

[0084] A method for preparing a wet-laid skeleton nonwoven fabric with long lifespan and high efficiency for catalytic degradation of volatile organic compounds (VOCs) includes the following preparation steps:

[0085] (1) Wet ion etching surface treatment: Keratin solution is sprayed onto the surface of fiber raw material and dried at a constant temperature after spraying; then crosslinking agent solution is sprayed and dried at a constant temperature. The crosslinking agent completes crosslinking during the constant temperature drying process; then the dried fiber raw material is immersed in acid solution and surface etching is performed by acid immersion. The areas not covered by keratin crosslinking are covered by a large number of micropores and mesopores due to the acid; then it is filtered and washed with water to remove excess acid from the fiber surface; then the fiber raw material is treated with alkaline washing to remove keratin. After alkaline washing, deionized water is used to wash away residual alkaline solution from the fiber surface.

[0086] (2) Plasma bombardment surface treatment: The fiber raw material obtained in step (1) is placed in a plasma device, vacuumed, and then nitrogen is used as the gas source to generate plasma by radio frequency inductive coupling to treat the fiber raw material.

[0087] (3) Preparation of self-assembled functional nanomaterials: The functional materials and nonionic surfactants were mixed in proportion and then added to a nanoball mill for grinding and dispersion to obtain self-assembled functional nanomaterials.

[0088] (4) Web forming: The fiber raw material obtained in step (2) and the self-assembled functional nanomaterial obtained in step (3) are stirred and loosened in the raw material tank in proportion to prepare a slurry. The slurry is then fully mixed with deionized water at a mass ratio of 20:100 and dehydrated in a forming inclined screen to obtain a fiber web. The temperature and pH value of the formed fiber web are then adjusted so that the functional nanomaterials can self-assemble in the fiber web.

[0089] (5) Coating and sizing: After adjusting the temperature and pH value, the formed fiber web is quickly coated and sizing is applied in a curtain manner. After the sizing is completed, the web is heated and cured.

[0090] (6) Post-processing: After the cured fiber web is washed with water, ultrasonically removed and defects removed, it is then subjected to thermal stretching and shaping to obtain the final product, wet-laid skeleton nonwoven fabric.

[0091] The keratin solution in step (1) has a mass concentration of 30%. The mass ratio of keratin solution to fiber raw material is 3:100; the constant temperature drying temperature is 35-60℃, and the time is 120 minutes. The crosslinking agent solution has a mass concentration of 40%, and the mass ratio of keratin to crosslinking agent is 1:5. The crosslinking agent is polyethylene glycol diglycidyl ether. The acid solution is nitric acid with a mass concentration of 15% or higher. The alkaline washing is performed at a temperature of 50-75℃ for 90 minutes, and the alkaline solution used is a 12% potassium hydroxide solution.

[0092] Step (1) The fiber raw materials are 10 mm long polyethylene terephthalate fiber (diameter 20 μm), 3 mm long polyethylene terephthalate fiber (diameter 24 μm) and 3 mm long vinylon fiber (diameter 18 μm), with a mass ratio of 5:2:2.5.

[0093] The vacuum pressure in step (2) is less than 100 Pa.

[0094] Step (2) control the radio frequency processing power to be 500W and the radio frequency to be 15MHz, and process for 300s at a temperature of 100℃.

[0095] Step (3) The functional material comprises titanate compound, sodium aluminate and chitosan in a mass ratio of 5:1:1; the titanate compound is tetrabutyl titanate; the nonionic surfactant is polyoxyethylene alkylamine; the mass ratio of the functional material and the nonionic surfactant is 100:3.

[0096] According to the mass ratio, the ratio of fiber raw materials and self-assembled functional nanomaterials in step (4) is: 16 mm long polyethylene terephthalate fiber: 5 mm long polyethylene terephthalate fiber: 5.2 mm long vinylon fiber: self-assembled functional nanomaterials = 5:2:2.5:0.5.

[0097] Step (4) Adjust the temperature to 60-75℃ and pH > 10.

[0098] In step (5), the adhesive solution is a co-solution mixture of hyperbranched polyamide amine and polyacrylic acid resin with a mass ratio of 12:1, and the curing temperature is 100-150℃.

[0099] Example 5

[0100] A method for preparing a wet-laid skeleton nonwoven fabric with long lifespan and high efficiency for catalytic degradation of volatile organic compounds (VOCs) includes the following preparation steps:

[0101] (1) Wet ion etching surface treatment: Keratin solution is sprayed onto the surface of fiber raw material and dried at a constant temperature after spraying; then crosslinking agent solution is sprayed and dried at a constant temperature. The crosslinking agent completes crosslinking during the constant temperature drying process; then the dried fiber raw material is immersed in acid solution and surface etching is performed by acid immersion. The areas not covered by keratin crosslinking are covered by a large number of micropores and mesopores due to the acid; then it is filtered and washed with water to remove excess acid from the fiber surface; then the fiber raw material is treated with alkaline washing to remove keratin. After alkaline washing, deionized water is used to wash away residual alkaline solution from the fiber surface.

[0102] (2) Plasma bombardment surface treatment: The fiber raw material obtained in step (1) is placed in a plasma device, vacuumed, and then nitrogen is used as the gas source to generate plasma by radio frequency inductive coupling to treat the fiber raw material.

[0103] (3) Preparation of self-assembled functional nanomaterials: The functional materials and nonionic surfactants were mixed in proportion and then added to a nanoball mill for grinding and dispersion to obtain self-assembled functional nanomaterials.

[0104] (4) Web forming: The fiber raw material obtained in step (2) and the self-assembled functional nanomaterial obtained in step (3) are stirred and loosened in the raw material tank in proportion to prepare a slurry. The slurry is then fully mixed with deionized water at a mass ratio of 23:100 and dehydrated in a forming inclined screen to obtain a fiber web. The temperature and pH value of the formed fiber web are then adjusted so that the functional nanomaterials can self-assemble in the fiber web.

[0105] (5) Coating and sizing: After adjusting the temperature and pH value, the formed fiber web is quickly coated and sizing is applied in a curtain manner. After the sizing is completed, the web is heated and cured.

[0106] (6) Post-processing: After the cured fiber web is washed with water, ultrasonically removed and defects removed, it is then subjected to thermal stretching and shaping to obtain the final product, wet-laid skeleton nonwoven fabric.

[0107] The keratin solution in step (1) has a mass concentration of 40%. The mass ratio of keratin solution to fiber raw material is 1:100; the constant temperature drying temperature is 35-60℃, and the time is 30 minutes. The crosslinking agent solution has a mass concentration of 50%, and the mass ratio of keratin to crosslinking agent is 1:10. The crosslinking agent is glutaraldehyde. The acid solution is nitric acid with a mass concentration of 15% or higher. The alkaline washing is performed at a temperature of 50-75℃ for 120 minutes, using concentrated ammonia solution.

[0108] Step (1) The fiber raw materials are polyethylene terephthalate fiber (diameter 20μm) with a length of 10mm, polyethylene terephthalate fiber (diameter 24μm) with a length of 3mm and vinylon fiber (diameter 18μm) with a length of 3mm, and the mass ratio of the three is 5:2.5:2.

[0109] The vacuum pressure in step (2) is less than 100 Pa.

[0110] Step (2) control the radio frequency processing power to be 600W and the radio frequency to be 10MHz, and process for 400s at a temperature of 110℃.

[0111] Step (3) The functional material comprises titanate compound, sodium aluminate and chitosan in a mass ratio of 3:3:1; the titanate compound is tetrabutyl titanate phosphate; the nonionic surfactant is castor oil polyoxyethylene ether and polyoxyethylene alkylolamide (mass ratio of 1:1); the mass ratio of the functional material and the nonionic surfactant is 100:2.5.

[0112] According to the mass ratio, the ratio of fiber raw materials and self-assembled functional nanomaterials in step (4) is: 18mm long polyethylene terephthalate fiber: 8mm long polyethylene terephthalate fiber: 8mm long vinylon fiber: self-assembled functional nanomaterials = 5:2.5:2:0.5.

[0113] Step (4) Adjust the temperature to 60-75℃ and pH > 10.

[0114] In step (5), the adhesive solution is a co-solution of hyperbranched polyamide amine and polyacrylic acid resin with a mass ratio of 15:1, and the curing temperature is 100-150℃.

[0115] Comparative Example 1

[0116] A method for preparing a wet-laid skeleton nonwoven fabric that catalytically degrades volatile organic compounds (VOCs) includes the following preparation steps:

[0117] (1) Plasma bombardment surface treatment: The fiber raw material is placed in a plasma device, and after vacuuming, nitrogen is used as the gas source to generate plasma by radio frequency inductive coupling to treat the fiber raw material.

[0118] (2) Preparation of self-assembled functional nanomaterials: The functional materials and nonionic surfactants were mixed in a certain proportion and then added to a nanoball mill for grinding and dispersion to obtain self-assembled functional nanomaterials.

[0119] (3) Web forming: The fiber raw material obtained in step (1) and the self-assembled functional nanomaterial obtained in step (2) are stirred and loosened in the raw material tank in proportion to prepare a slurry. The slurry is then fully mixed with deionized water at a mass ratio of 23:100 and dehydrated in a forming inclined screen to obtain a fiber web. The temperature and pH value of the formed fiber web are then adjusted so that the functional nanomaterials can self-assemble in the fiber web.

[0120] (4) Coating and sizing: After adjusting the temperature and pH value, the formed fiber web is quickly coated and sizing is applied in a curtain manner. After the sizing is completed, the temperature is raised and cured.

[0121] (5) Post-processing: After the cured fiber web is washed with water, ultrasonically removed and defects removed, it is then subjected to thermal stretching and shaping to obtain the final product, wet-laid skeleton nonwoven fabric.

[0122] In this comparative example, except that wet ion etching surface treatment was not performed, the raw materials and preparation methods were the same as in Example 5.

[0123] Comparative Example 2

[0124] A method for preparing a wet-laid skeleton nonwoven fabric that catalytically degrades volatile organic compounds (VOCs) includes the following preparation steps:

[0125] (1) Wet ion etching surface treatment: Keratin solution is sprayed onto the surface of fiber raw material and dried at a constant temperature after spraying; then crosslinking agent solution is sprayed and dried at a constant temperature. The crosslinking agent completes crosslinking during the constant temperature drying process; then the dried fiber raw material is immersed in acid solution and surface etching is performed by acid immersion. The areas not covered by keratin crosslinking are covered by a large number of micropores and mesopores due to the acid; then it is filtered and washed with water to remove excess acid from the fiber surface; then the fiber raw material is treated with alkaline washing to remove keratin. After alkaline washing, deionized water is used to wash away residual alkaline solution from the fiber surface.

[0126] (2) Preparation of self-assembled functional nanomaterials: The functional materials and nonionic surfactants were mixed in a certain proportion and then added to a nanoball mill for grinding and dispersion to obtain self-assembled functional nanomaterials.

[0127] (3) Web forming: The fiber raw material obtained in step (1) and the self-assembled functional nanomaterial obtained in step (3) are stirred and loosened in the raw material tank in proportion to prepare a slurry. The slurry is then fully mixed with deionized water at a mass ratio of 23:100 and dehydrated in a forming inclined screen to obtain a fiber web. The temperature and pH value of the formed fiber web are then adjusted so that the functional nanomaterial can self-assemble in the fiber web.

[0128] (4) Coating and sizing: After adjusting the temperature and pH value, the formed fiber web is quickly coated and sizing is applied in a curtain manner. After the sizing is completed, the temperature is raised and cured.

[0129] (5) Post-processing: After the cured fiber web is washed with water, ultrasonically removed and defects removed, it is then subjected to thermal stretching and shaping to obtain the final product, wet-laid skeleton nonwoven fabric.

[0130] In this comparative example, except for the absence of plasma bombardment surface treatment, the raw materials and preparation methods are the same as in Example 5.

[0131] Comparative Example 3

[0132] A method for preparing a wet-laid skeleton nonwoven fabric that catalytically degrades volatile organic compounds (VOCs) includes the following preparation steps:

[0133] (1) Wet ion etching surface treatment: Keratin solution is sprayed onto the surface of fiber raw material and dried at a constant temperature after spraying; then crosslinking agent solution is sprayed and dried at a constant temperature. The crosslinking agent completes crosslinking during the constant temperature drying process; then the dried fiber raw material is immersed in acid solution and surface etching is performed by acid immersion. The areas not covered by keratin crosslinking are covered by a large number of micropores and mesopores due to the acid; then it is filtered and washed with water to remove excess acid from the fiber surface; then the fiber raw material is treated with alkaline washing to remove keratin. After alkaline washing, deionized water is used to wash away residual alkaline solution from the fiber surface.

[0134] (2) Plasma bombardment surface treatment: The fiber raw material obtained in step (1) is placed in a plasma device, vacuumed, and then nitrogen is used as the gas source to generate plasma by radio frequency inductive coupling to treat the fiber raw material.

[0135] (3) Web forming: The fiber raw materials and functional materials obtained in step (2) are stirred and loosened in the raw material tank in proportion to prepare a slurry. The slurry is then fully mixed with deionized water at a mass ratio of 23:100 and dehydrated in a forming inclined screen to obtain a fiber web. The temperature and pH value of the formed fiber web are then adjusted.

[0136] (4) Coating and sizing: After adjusting the temperature and pH value, the formed fiber web is quickly coated and sizing is applied in a curtain manner. After the sizing is completed, the temperature is raised and cured.

[0137] (5) Post-processing: After the cured fiber web is washed with water, ultrasonically removed and defects removed, it is then subjected to thermal stretching and shaping to obtain the final product, wet-laid skeleton nonwoven fabric.

[0138] The functional material in step (3) is a titanate compound, specifically tetrabutyl titanate phosphate.

[0139] In step (4), the ratio of fiber raw materials to self-assembled functional nanomaterials is: 18mm long polyethylene terephthalate fiber: 8mm long polyethylene terephthalate fiber: 8mm long vinylon fiber: functional material = 5:2.5:2:0.5.

[0140] In this comparative example, except that the self-assembly of functional materials is not performed, the raw materials and preparation methods are the same as in Example 5.

[0141] Comparative Example 4

[0142] The specific operating method for conventional wet-laid skeleton nonwoven fabric is as follows:

[0143] The product comprises, by weight, 30-60 parts of polyethylene terephthalate with a fineness of 6-10 dtex, 30-40 parts of polyacrylic acid resin, 12-15 parts of hyperbranched polyamide amine, and 1-2 parts of additives.

[0144] The additives are polyethylene oxide dispersants or polyether defoamers.

[0145] The following steps are used to prepare the above-mentioned nonwoven fabric:

[0146] a. Polyethylene terephthalate fiber and auxiliaries are stirred in water to prepare a slurry;

[0147] b. The slurry and deionized water are thoroughly mixed at a mass ratio of 23:100 and then dehydrated and shaped using an inclined screen.

[0148] c. The formed fiber web is coated with sizing solution using a curtain coating method. The sizing solution is a co-solution mixture of formaldehyde remover hyperbranched polyamide amine and polyacrylic acid resin.

[0149] The fabric is dried and cured in an oven to form a nonwoven fabric. A horizontal quantitative scanner is used to monitor the main physical properties of the nonwoven fabric, such as its basis weight and thickness, and then it is rolled into a roll.

[0150] Performance testing

[0151] Test method:

[0152] Reference national standards

[0153] GB 6529 Standard Atmospheres for Conditioning and Testing of Textiles

[0154] GB / T 4669 Mass per unit length and mass per unit length of woven fabrics

[0155] Area measurement

[0156] GB / T 3820 Determination of thickness of textiles and textile products

[0157] GB / T 3923.1 Determination of breaking strength and elongation at break of fabrics (strip method)

[0158] GB / T 5453 Determination of air permeability of textiles and fabrics

[0159] GB / T 18318.3 Determination of bending properties of textiles (Glydell method)

[0160] GB / T 10342 Packaging and Marking of Paper

[0161] GB / T 450 Sampling of Paper and Paperboard Samples

[0162] Fiber fineness: analyzed by scanning electron microscopy

[0163] The test results are shown in Table 1:

[0164] Table 1 Performance Test Results

[0165]

[0166]

[0167] As can be seen from the data in Table 1, the wet-laid skeleton nonwoven fabrics obtained in Examples 1-5 of this invention exhibit good mechanical properties, stiffness, and air permeability. However, the properties of Comparative Examples 1-3 (with modified preparation steps) and Comparative Example 4 (with conventional wet-laid nonwoven fabric) all showed varying degrees of decline.

[0168] Further testing of VOCs purification effects was conducted, referring to the method GB / T 23761-2020 "Test Methods for Air Purification Performance of Photocatalytic Materials and Products - Degradation of Acetaldehyde (or Formaldehyde)".

[0169] The test results are shown in Table 2:

[0170] Table 2 Performance Test Results

[0171]

[0172] As can be seen from the data in Table 2, Examples 1-5 of the present invention exhibited a durable and stable formaldehyde and acetaldehyde degradation effect, and maintained a catalytic degradation rate of over 90% even after 48 months of stable use. However, Comparative Examples 1-3, which lacked surface treatment, and Comparative Example 3, which did not undergo self-assembly of functional materials, as well as conventional wet-laid nonwoven fabric materials, showed significantly weaker catalytic degradation effects. This is because the two-step surface modification method and the preparation of self-assembled functional materials are key technical means affecting the titanium dioxide loading effect; the three complement each other and form an organically unified whole, and the absence of any one of them weakens the effect.

[0173] It should be noted that the above embodiments are merely some preferred embodiments of the present invention, and not all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a wet-laid skeleton nonwoven fabric with long lifespan and high efficiency for catalytic degradation of volatile organic compounds (VOCs), characterized in that, The preparation steps include the following: (1) Wet ion etching surface treatment: spray keratin solution onto the surface of fiber raw material, and dry at constant temperature after spraying; then spray crosslinking agent solution, and dry at constant temperature; then soak the dried fiber raw material in acid solution, filter, wash with water to remove excess acid from the fiber surface; then treat the fiber raw material with alkaline washing, and after alkaline washing, wash with deionized water to remove residual alkaline from the fiber surface. (2) Plasma bombardment surface treatment: The fiber raw material obtained in step (1) is placed in a plasma device, and after vacuuming, nitrogen is used as the gas source to generate plasma by radio frequency inductive coupling to treat the fiber raw material. (3) Preparation of self-assembled functional nanomaterials: The functional materials and nonionic surfactants were mixed in proportion and then added to a nanoball mill for grinding and dispersion to obtain self-assembled functional nanomaterials. (4) Web forming: The fiber raw material obtained in step (2) and the self-assembled functional nanomaterial obtained in step (3) are stirred and loosened in the raw material tank in proportion to prepare a slurry. The slurry is then fully mixed with deionized water and dehydrated and formed in a forming inclined screen to obtain a fiber web. The temperature and pH value of the formed fiber web are then adjusted so that the functional nanomaterial can self-assemble in the fiber web. (5) Coating and applying adhesive: After adjusting the temperature and pH value, quickly apply adhesive to the fiber web in a curtain-like manner. After the adhesive is applied, heat up and cure. (6) Post-processing: After the cured fiber web is washed with water, ultrasonically removed and defects removed, it is then subjected to thermal stretching and shaping to obtain the final product, wet-laid skeleton nonwoven fabric. In step (1), the mass concentration of the keratin solution is 10-40%; the mass ratio of the keratin solution to the fiber raw material is (1-3):100; the constant temperature drying temperature is 35-60℃, and the time is 30-180 minutes; the mass concentration of the crosslinking agent solution is 20-50%, and the mass ratio of keratin to crosslinking agent is 1:(1-10), wherein the crosslinking agent is a dialdehyde compound or a diglycidyl ether compound; the acid solution is one or a combination of sulfuric acid with a mass concentration of 30% or more, phosphoric acid with a mass concentration of 50% or more, hydrochloric acid with a mass concentration of 15% or more, and nitric acid with a mass concentration of 15% or more; the alkaline washing temperature is 50-75℃, and the time is 30-120 minutes, wherein the alkaline solution used is one or more of concentrated ammonia, sodium hydroxide solution with a mass concentration of 5-15%, and potassium hydroxide solution with a mass concentration of 5-15%; Step (3) The functional material comprises titanate compounds, sodium aluminate and chitosan, with a mass ratio of (3-5):(0-3):1; the titanate compounds are tetrabutyl titanate and / or tetrabutyl titanate phosphate; the nonionic surfactant is one or more of long-chain fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine, and polyoxyethylene alkylolamide; the mass ratio of the functional material and the nonionic surfactant is 100:(2.5-5); Step (4) The temperature is adjusted to 60-75℃ and the pH is >10.

2. The method for preparing a wet-laid nonwoven fabric with a long lifespan and high efficiency for catalytic degradation of volatile organic compounds (VOCs) according to claim 1, characterized in that, Step (1) The fiber raw materials are polyethylene terephthalate fibers with a length of 10-18 mm, polyethylene terephthalate fibers with a length of 3-10 mm and vinylon fibers with a length of 3-10 mm, and the mass ratio of the three is (3-6):(1-3):(2-3).

3. The method for preparing a wet-laid nonwoven fabric with a long lifespan and high efficiency for catalytic degradation of volatile organic compounds (VOCs) according to claim 1, characterized in that, Step (2) control the radio frequency processing power to be 200-1000W and the radio frequency to be 8-15MHz, and process for 100-600s under the condition of 30-110℃.

4. The method for preparing a wet-laid nonwoven fabric with a long lifespan and high efficiency for catalytic degradation of volatile organic compounds (VOCs) according to claim 1, characterized in that, According to the mass ratio, the amount of fiber raw materials and self-assembled functional nanomaterials used in step (4) is: 10-18 mm long polyethylene terephthalate fiber: 3-10 mm long polyethylene terephthalate fiber: 3-10 mm long vinylon fiber: self-assembled functional nanomaterials = (3-6): (1-3): (2-3): (0.1-2).

5. The method for preparing a wet-laid nonwoven fabric with a long lifespan and high efficiency for catalytic degradation of volatile organic compounds (VOCs) according to claim 1, characterized in that, In step (5), the adhesive solution is a co-solution of hyperbranched polyamide amine and polyacrylic acid resin, with a mass ratio of (8-15):1, and the curing temperature is 100-150℃.

6. A nonwoven fabric prepared according to any one of claims 1-5.

7. The use of the nonwoven fabric of claim 6 in the preparation of an air filter.

Citation Information

Patent Citations

  • Photocatalyst spun-bonded non-woven fabric and preparation method thereof

    CN115404597A

  • Formaldehyde-removing air filtering material

    CN218687885U

  • Formula and preparation process of aldehyde-removal wet-process aggregate non-woven fabric

    CN107815916A